2011
DOI: 10.1111/j.1399-3089.2011.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically‐modified pig mesenchymal stromal cells: xenoantigenicity and effect on human T‐cell xenoresponses

Abstract: Genetically modified pMSC is significantly less immunogenic than WT pMSC. GTKO/CD46 pMSC downregulates the human T-cell responses to pig antigens as efficiently as human MSC, which can be advantageous for therapeutic cell xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
0
30
0
1
Order By: Relevance
“…Studies by Wilhite et al have demonstrated a significant reduction in the primate mixed lymphocyte reaction to pig ECs when Gal is absent or an hCRP is expressed (54,55) (Figure 3). Although there is a definite reduction in the human T cell proliferative response to GTKO/hCRP pig cells in vitro, it is difficult to quantify this effect in vivo in pig-to-NHP transplantation models as so many other factors, e.g., coagulation dysregulation, affect the outcome.…”
Section: Suppression Of the Immune Responsesmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies by Wilhite et al have demonstrated a significant reduction in the primate mixed lymphocyte reaction to pig ECs when Gal is absent or an hCRP is expressed (54,55) (Figure 3). Although there is a definite reduction in the human T cell proliferative response to GTKO/hCRP pig cells in vitro, it is difficult to quantify this effect in vivo in pig-to-NHP transplantation models as so many other factors, e.g., coagulation dysregulation, affect the outcome.…”
Section: Suppression Of the Immune Responsesmentioning
confidence: 96%
“…Although encouraging in vitro data have been reported, the immunomodulatory efficacy of regulatory T cells (Tregs) (10,91,92) or MSCs (55,93,94) has yet to be demonstrated in large animal models of xenotransplantation. Tregs have been demonstrated to suppress the xenoreactive effector T cell response in vitro , as have MSCs.…”
Section: Cell Therapy Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…High CD55 expression levels have already been shown to inhibit NK cell activation (Miyagawa et al, 2004). CD46 expression has significant effects on inhibition of procoagulant and antifibrinolytic pathways (Bongoni et al, 2015) and a combination of GGTA1 knockout and CD46 expression was shown to down-regulate the human T-cell response to porcine cells (Ezzelarab et al, 2011;Wilhite et al, 2012). A20 expression also inhibits T-cell activation (Coornaert et al, 2008).…”
Section: Multi-transgenic Animalsmentioning
confidence: 99%
“…33 Accompanying in vitro studies indicated that the overexpression of human TFPI by pig bone marrow-derived mesenchymal stromal cells inhibited clotting, which is an observation that may be of potential therapeutic importance and warrants further investigation. 34,35 …”
Section: Introductionmentioning
confidence: 99%